KOMUNIKASI RITUAL DALAM UPACARA TAWUR LABUH GENTUH DI TAMAN MAYURA KOTA MATARAM - I Nyoman Buda Asmara Putra (UHN IGB Sugriwa Denpasar, 2021)
Communication is a fundamental need in human life. Bycommunicating, humans interact with God, fellow humans and the naturalenvironment to establish a harmonious life. Hindus in West Nusa Tenggaracarry out a tawur labuh gentuh ceremony at Mayura Park, Mataram Cityimplementing the tri hita karana concept. In the process of implementingthe tawur labuh gentuh ceremony, communication dynamics occur usingsymbols that need to be understood together. This study, entitled